Semi-analytical BEM-FEM analysis of SDCM wall as passive wave barrier in saturated soil - Xiang Zhu; Gang Shi; Xinjun Gao; Hao Zhang; Song Wang; Guangyun Gao (Results in Engineering, 2025)
This study proposes a novel environmentally friendly wave barrier, the Stiffened Deep Cement Mixing (SDCM) wall, for mitigating ground vibrations in saturated soils. An in-site measurement of ground vibrations due to the metro-train in Shanghai was introduced and the dominant frequency of ground vibrations was analyzed. Then the feasibility of using SDCM wall as wave barrier was discussed, and an in-situ validation test confirmed the feasibility and vibration reduction capability of SDCM walls. Further, a three-dimensional coupled semi-analytical BEM-FEM model was developed to analyze the passive vibration isolation effectiveness of SDCM walls against incident Rayleigh waves in saturated soil. And the model incorporates a parallel SPMD algorithm for efficiency and addresses corner discontinuities using a multi-value-node method. The effects of the model parameters on isolation effectiveness were investigated and discussed in detail. The results show that SDCM walls successfully isolate ground vibrations, with core piles (PHC/PHS) playing a critical role. Optimal performance is achieved when core pile depth matches the DCM wall depth, cross-sections are large, and pile holes remain empty. When the length of SDCM wall is constant, one can obtain a better screening efficiency and the less number of core piles by appropriately increasing the net spacing between piles. Moreover, the SDCM wall length should be sufficiently large to protect target structures, and a depth exceeding 1.0λR(Rayleigh wavelength) ensures effectiveness without requiring excessive depth.